Northern Hemisphere Extra-Tropics 2,000-year Decadal Temperature Reconstruction - Christiansen, Bo; Charpentier Ljungquist, Fredrik (Danish Meteorological Institute, 2019)
Multi-proxy temperature reconstruction for the extra-tropical Northern Hemisphere (90-30°N) during the last two millennia based on 30 palaeotemperature proxy records with annual to multi-decadal resolution. Proxy types include historical documentary records, seafloor sediment records, lake sediment records, speleothem records, ice-core records, varved thickness sediment records, tree-ring width and maximum latewood density records. The reconstruction is presented as decadal anomalies in degrees C relative to the 1961-1990 reference period and provided with quantitative error bars.

The dataset can be downloaded from:
https://www.ncei.noaa.gov/metadata/geoportal/rest/metadata/item/noaa-recon-9924/html

Temperaturrekonstruktion för den extratropiska norra halvklotet.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0085

Datasatsen kan laddas ner från:
https://www.ncei.noaa.gov/metadata/geoportal/rest/metadata/item/noaa-recon-9924/html
2000 års dekadaltemperaturrekonstruktion för den extratropiska norra halvklotet
Keywords: COMMON SENSE CLIMATE INDEX; AIR TEMPERATURE RECONSTRUCTION; CLIMATE INDICATORS; Natural Sciences; Naturvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi